A novel guidance scheme for close range operation in active debris removal. Issue 1 (March 2018) - Wang, Weilin; Song, Xumin; Li, Kebo; Chen, Lei
Abstract: Active debris removal mission poses new challenge for close range guidance system design because the target debris is uncooperative and uncommunicative. The challenge is particularly critical if the debris is tumbling. Fly-around phase is an essential component of close range operation and provides precondition for target characterization, inspection and clamp capture. Although related study has been studied in rendezvous and formation flying, technology readiness is still low for application in active debris removal (ADR) and key technology is still under demonstration. Nutation following fly-around is proposed in this paper to define the forced motion which synchronizes chaser with tumbling target. Total synchronization will be necessary for debris capture, e.g. capture by rigid contact robotic arm. The contribution of this paper is to develop a novel dynamic model governing the relative motion between chaser and target and to design the guidance algorithm. Rotating LOS (Line of Sight) coordinate system is established with origin set at the chaser. Instant Rotating Plane of LOS (IRPL) is introduced to simplify the kinematic equations of tumbling motion based on differential geometric theory. Introduction of IRPL resolves the coupling effect between pitch and yaw planes in general 3D scenario and simplifies the control of chaser with a concise dynamical model. Two classical cases are presented to illustrate nutation following fly-around and simulations are implemented to demonstrate the effectiveness of proposed guidance scheme. Further study of proximity mission along spin axis is conducted to show the advantages of guidance scheme.